Myosin‐Binding Protein C DNA Variants in Domestic Cats (A31P, A74T, R820W) and their Association with Hypertrophic Cardiomyopathy. (17th January 2013) - Longeri, M.; Ferrari, P.; Knafelz, P.; Mezzelani, A.; Marabotti, A.; Milanesi, L.; Pertica, G.; Polli, M.; Brambilla, P.G.; Kittleson, M.; Lyons, L.A.; Porciello, F.
<x xml:space="preserve">Abstract</x> Background Two mutations in the MYBPC3 gene have been identified in Maine Coon (MCO) and Ragdoll (RD) cats with hypertrophic cardiomyopathy (HCM). Objective This study examined the frequency of these mutations and of the A74T polymorphism to describe their worldwide distribution and correlation with echocardiography. Animals: 1855 cats representing 28 breeds and random‐bred cats worldwide, of which 446 underwent echocardiographic examination. Methods This is a prospective cross‐sectional study. Polymorphisms were genotyped by Illumina VeraCode GoldenGate or by direct sequencing. The disease status was defined by echocardiography according to established guidelines. Odds ratios for the joint probability of having HCM and the alleles were calculated by meta‐analysis. Functional analysis was simulated. Results The MYBPC3 A31P and R820W were restricted to MCO and RD, respectively. Both purebred and random‐bred cats had HCM and the incidence increased with age. The A74T polymorphism was not associated with any phenotype. HCM was most prevalent in MCO homozygote for the A31P mutation and the penetrance increased with age. The penetrance of the heterozygote genotype was lower (0.08) compared with the P/P genotype (0.58) in MCO. Conclusions and Clinical Importance A31P mutation occurs frequently in MCO cats. The high incidence of HCM in homozygotes for the mutation supports the causal nature of the A31P mutation. Penetrance is incomplete for heterozygotes at A31P locus, at least at a young age. The A74T variant does not appear to be correlated with HCM.